2017
DOI: 10.1016/j.exer.2017.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Equatorial wrinkles in the human lens capsule

Abstract: Equatorial wrinkles, or crenations, have been previously observed around the equator in coronal images of the human ocular lens. However, wrinkles are typically not apparent when the lens is viewed from saggital directions. In the current paper, the existence and geometry of these wrinkles is shown to be consistent with a mechanical model of the isolated lens, in which the capsule is held in a state of residual tension by a spatially uniform internal pressure. The occurrence of equatorial wrinkles is therefore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…127 and anisotropic strains have been found to exist in the intact human lens capsule near the equator, coinciding with the GZ. 128 It has also been observed that PCO can be inhibited in vitro by using pharmaceutical agents targeting the cytoskeleton. 129 The cytoskeleton is typically involved in transducing external mechanical cues.…”
Section: Lec Mediated Lens Regenerationmentioning
confidence: 99%
“…127 and anisotropic strains have been found to exist in the intact human lens capsule near the equator, coinciding with the GZ. 128 It has also been observed that PCO can be inhibited in vitro by using pharmaceutical agents targeting the cytoskeleton. 129 The cytoskeleton is typically involved in transducing external mechanical cues.…”
Section: Lec Mediated Lens Regenerationmentioning
confidence: 99%
“…21 Such anisotropic strains have been found to exist in the intact human lens capsule near the equator, coinciding with the region in which proliferation is known to occur in the mouse lens. 3,22 PCO can be inhibited in vitro by using pharmaceutical agents targeting the cytoskeleton 23 ; the cytoskeleton is known to convey information about mechanical stresses on a cell to the nucleus resulting in changes in protein expression. 24 Together, these results suggest that LECs are strain-responsive cells (i.e., they can alter their behavior in response to mechanical cues from their environment).…”
mentioning
confidence: 99%
“…Choroidal folding presumably results from a loss of tension in the direction perpendicular to wrinkling. This is a geometric phenomenon and would therefore be driven by globe flattening: as the principal radii of curvature change, tension in an inflated membrane (e.g., the choroid) can be lost ( Burd et al, 2017 ). Once tension is removed, these folds may be permanent ( Cassidy and Sanders, 1999 ).…”
Section: Discussionmentioning
confidence: 99%